(untitled) (Eurasian Research Bulletin, 2022)
Oscillation processes in nature are described by differential equations. Further studies show that many biological processes can be reduced to fractional differential equations. Therefore, the study of such equations and the problems posed to them has important theoretical and practical significance. This article deals with Mellin’s integral substitution and its applications.